Spectral analysis of discrete dirac equation with generalized eigenparameter in boundary condition - Koprubasi, Turhan; Mohapatra, Ram N. (National Library of Serbia, 2019)
Let L denote the discrete Dirac operator generated in ?2 (N,C2) by the non-selfadjoint difference operators of first order (an+1y(2)n+1 + bny(2)n + pny(1)n = ?y(1)n, an-1y(1)n-1 + bny(1)n + qny(2)n = ?y(2)n, n ? N, (0.1) with boundary condition Xp k=0 (y(2)1?k + y(1)0 ?k)?k=0, (0.2) where (an), (bn), (pn) and (qn), n ? N are complex sequences, ?i; ?i ? C, i = 0, 1, 2,..., p and ? is a eigenparameter. We discuss the spectral properties of L and we investigate the properties of the spectrum and the principal vectors corresponding to the spectral singularities of L, if ?? n=1 |n|(|1-an| + |1+bn| + |pn| + |qn|) < ? holds.
Keywords: discrete spectrum; spectral singularities; Eigenvalue problems for linear operators; eigenparameter; principal functions; Difference operators; Spectrum, resolvent; discrete Dirac equations; spectral analysis; 4. Education